Acoustic emission evaluation and localization correction of concrete damage considering stress levels - Xiuxin Li; Tianjiao Miao; Tao Liu; Rengan Chen; Aiping Yu (Case Studies in Construction Materials)
The key focus of acoustic emission technology is the precision in evaluating concrete damage and pinpointing damage sources. This study proposes a method for correcting the acoustic emission evaluation of concrete under different stress levels. The validation was conducted through uniaxial graded loading tests on six groups of concrete samples with particle sizes of 4.75–9.5 mm, 9.5–16 mm, 16–19 mm, 19–26.5 mm, 26.5–31.5 mm, and continuous particle size. The results show that the AE elastic wave velocity has a strong correlation with the stress levels. The larger the coarse aggregate size of the samples, the smaller the final wave velocity in the instability stage. Based on the evolution law of wave velocity standard deviation Sv, the damage value Dv, and the AE energy, the damage process of concrete can be more accurately divided into four stages: the initial stage (I), the stable crack development stage (Ⅱ′), the rapid crack expansion stage (Ⅱ′′), and the instability and failure stage (Ⅲ). An Sv value of 1850 indicates that concrete is nearing the phase of stable failure, offering a benchmark to assess its serviceability. Compared to the traditional steady-state wave velocity localization methods, considering velocity attenuation in the localization correction method results in higher precision for reflecting crack morphology, increasing localization accuracy by 27.609 %.